Gandasari Gandawangi Dance: The Transformation of Legendary Form Into Tourism Arts in Jalawastu Brebes - Turyati; Widyaningrum, Septiana Yustika (Institut Seni Indonesia Denpasar, 2024)
This article traces the transformation process of the legend of the characters Gandasari and Gandawangi into Gandasari Gandawangi Dance, created as a tourism performing art in Jalawastu Traditional Village, Brebes, Central Java. The legend narrates the story of a civil war among prominent figures embracing Islam in that region. From this narrative, a dance and music performance with an innovative tourism package highlighting Jalawastu Traditional Village's local wisdom was realized. The research methodology employed in this study is qualitative with an ethnographic approach. Data collection techniques encompassed interviews, documentary studies, and field observations. Observations were conducted to gather data, which was subsequently analyzed to formulate the transformation process and understand the significance of the Gandasari Gandawangi Dance. This article concludes that Gandasari Gandawangi Dance is adapted from the legend and further developed with creative dance movements, thereby serving as a tourism performing art that is expected to enhance the tourism potential of Jalawastu Traditional Village.